C-reactive protein/albumin ratio in patients with multiple sclerosis and its relationship with disease subtype and disability - Eren, Fettah; Demir, Aysegul (Journal of Surgery and Medicine, 2020)
Aim: Oxidative stress and inflammation are the cause of demyelination and axonal damage in patients with Multiple Sclerosis (MS). Serum C-reactive protein (CRP) and albumin levels are used as a marker of systemic inflammation and oxidative stress for many diseases. In this study, we aimed to determine the level of CRP/albumin ratio in patients with MS and its relationship with disease subtype and disability. Methods: This cross-sectional study was conducted in patients treated for MS disease. One hundred twenty MS patients and 62 healthy controls were included. Sociodemographic characteristics were questioned. MS subtype was determined. Disability was calculated with Expanded Disability Status Scale (EDSS). Patients were divided into 3 groups: EDSS 0-3 (minor), 3.5-4.5 (moderate) and 5.0 or higher (major). Attack frequency, albumin and CRP serum levels were noted, and hemogram was analyzed with fluorescence flow cytometry. Results: There were 71 (59.2%) female and 49 (40.8%) male patients in the study, and their mean age was 39.49 (11.47) years. Leukocyte value was higher and albumin was lower in patients with MS (P=0.046, P=0.006). In progressive MS patients, CRP and CRP/albumin ratio was higher and albumin level was lower compared to the relapse remitting subtype (P<0.01). Patients with high EDSS had higher CRP and CRP/albumin ratio and lower albumin levels (P<0.01). A low correlation was detected between the number of attacks and CRP/albumin ratio (P=0.032; r=0.196). Conclusion: We detected that albumin level and CRP/albumin ratio are related with subtype and activity of MS disease.